PENGEMBANGAN PROFIL SEKOLAH BERBASIS WEBSITE MENGGUNAKAN METODE OBJECT ORIENTED ANALYSIS AND DESIGN - Nyimas Sopiah; Wawan Didit M (Jurnal Ilmiah Matrik, 2021)
The school profile is one of the most important things in promoting a school. By displaying a school profile, visitors from a school can see all teaching and learning activities in a school. This is very important considering the school profile is also a promotional medium that can be displayed to others. In developing this school profile, the author is interested in making it use a website using analysis methods and object-oriented design. One of the objects chosen is SMK Istiqlal Palembang, which so far has no school profile using the website, so it is hoped that it can become a promotional media for prospective students who want to enter this school. The programming language used is PHP and the database used is My SQL.